2016
DOI: 10.1007/s00226-016-0871-8
|View full text |Cite
|
Sign up to set email alerts
|

Tartaric acid catalyzed furfurylation of beech wood

Abstract: European beech (Fagus sylvatica L.) is a major tree species of European forest which is underexploited because of its low dimensional stability and durability. Similarly to what has been developed with radiata pine, furfurylation might be the answer to optimize the utilization of local beech wood. Beech wood furfurylation process was studied using five different catalysts: maleic anhydride, maleic acid, citric acid, itaconic acid, and tartaric acid. Optimization of the furfurylation process was investigated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 29 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…In contrast, higher WPGs appeared in furfurylation of Masson pine and Camphor pine wood, ranging between 20.9% to 35.9% and 37.9% to 44.4% with averages of 25.2% and 39.2%, respectively Esteves et al (2011). treated Pinus pinaster with a 70% FA mixture and found an average WPG of 38% Sejati et al (2017). reported that the WPG of European beech (Fagus sylvatia L.) furfurylated with 50% FA and 5% tartaric acid catalyst was 40.7% for larger samples.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, higher WPGs appeared in furfurylation of Masson pine and Camphor pine wood, ranging between 20.9% to 35.9% and 37.9% to 44.4% with averages of 25.2% and 39.2%, respectively Esteves et al (2011). treated Pinus pinaster with a 70% FA mixture and found an average WPG of 38% Sejati et al (2017). reported that the WPG of European beech (Fagus sylvatia L.) furfurylated with 50% FA and 5% tartaric acid catalyst was 40.7% for larger samples.…”
mentioning
confidence: 93%
“…The authors have proposed a composite acidic catalyst for wood furfurylation in a previous study, which produced furfurylated wood with excellent mechanical and durable properties comparable to the widely used maleic anhydride, with less required FA and a lower cost (Li et al 2015). Recently, Sejati et al (2017) studied furfurylation of beech wood using five different catalysts; in addition to citric acid and maleic anhydride, maleic acid, itaconic acid, and tartaric acid were also studied. They indicated that tartaric acid can be considered as a new promising catalyst to perform wood furfurylation.…”
Section: Introductionmentioning
confidence: 99%
“…Furfurylated wood has light to dark brown colors, depending on the amount of weight percent gain (WPG) due to the loading of FA resin. Furfuryl alcohol, as well as acid catalyst, buffering agent, and water or ethanol (as solvent) is needed for the wood furfurylation process (Sejati et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been reported on physical properties, mechanical properties, and modification mechanisms, etc. of wood by furfurylation [ 27 , 28 , 29 , 30 ]. However, little is known about the hierarchical porous structure for furfurylated wood.…”
Section: Introductionmentioning
confidence: 99%